Is tree shelter protection an effective complement to weed competition management in improving the morpho-physiological response of holm oak planted seedlings? - Ceacero, Carlos J; Navarro-cerrillo, Rafael M; Díaz-Hernández, José Luis (iForest - Biogeosciences and Forestry, 2014)
Weed control is a key aspect that influences seedling response in newly-established plantations. Tree shelter protection may be an effective complement to weed control with a positive effect on the overall response of seedlings. Our study focused on assessing the morpho-physiological response of Holm oak (Quercus ilex L. ballota [Desf.] Samp.) plantations to weed control and individual protection as a combined cultural technique on a cropland site in southern Spain. The weed control treatments (cultivation, herbicide and mulch) were also applied in combination with tree shelters. Morpho-physiological variables including survival, aerial and root morphology, water potential, gas exchange and chlorophyll fluorescence were monitored over a 2-year period. Results showed that weed competition management treatments improved the seedling survival rate compared to the control treatment. Moreover, shelter was associated with a greater height growth. At early stages of establishment, and particularly under combined treatments, all plants invested more resources in their aerial parts than in their root system. Seedlings did not regulate water loss as a result of water stress, contrary to what would be expected in Mediterranean areas. Under all treatments, especially those combined with tree shelters, seedlings took up to 2 years to achieve morpho-physiological adaptation (i.e. height and diameter growths, water stress behavior) to site conditions. In addition, tree shelters promoted an increase in net photosynthesis compared to non-shelter treatments during the winter period. The tree shelters also limited the emergence of photo-inhibition phenomena in seedlings so that plants under combined treatments showed greater photo-chemical efficiency. Thus, this study supports the effectiveness of tree shelter protection as a complement to weed control treatments. More specifically, it suggests that combining individual protection (shelter) and weed control around seedlings is an interesting technique for reforestation of forest ecosystems in Mediterranean areas.
Keywords: Mulch; Oxyfluorfen; photoinhibition; photosynthesis; Tillage; tree shelter

Interactions between soil gravel content and neighboring vegetation control management in oak seedling establishment success in Mediterranean environments - Ceacero, Carlos J; Díaz-Hernández, José Luis; del Campo, Antonio D; Navarro-cerrillo, Rafael M (Forest Ecology and Management, 2012)
Restoration of vegetation in Mediterranean areas is limited by several factors, some of which are poorly understood, such as soil stoniness and competition with natural vegetation. This paper analyzes the interaction between weed management treatments (cultivation, herbicide, mulch and tree shelter) and the proﬁle stoniness in Holm oak (Quercus ilex L. sub. ballota (Desf.) Samp.) seedling establishment in Mediterranean areas. Our experimental trials show that proﬁle gravel content is a key factor in seedling survival, in which optimal reforestation sites would be deﬁned by gravel content <5%; transitional sites by 5% 6 gravel content 6 15% and excluded sites by gravel content >15%. The soil proﬁle gravel content caused severe water limitations, especially important in the ﬁrst year after planting, which inﬂuenced the effectiveness of neighboring vegetation control techniques for seedling establishment success. This study also conﬁrms the positive effect of competition management techniques on survival. The treatments tested showed an improvement in the survival rate, but not in growth rate, over the control treatment throughout the monitoring period. We have obtained a vegetation response model in which the beneﬁcial effects of competition control on the success of oak seedling establishment are distorted by soil gravel content.
Keywords: Quercus ilex; Rock fragment; Soil water content; Vegetation establishment